2006
DOI: 10.1029/2005wr004707
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the effect of hydrograph characteristics on vertical grain sorting in gravel bed rivers

Abstract: [1] Desert ephemeral gravel bed streams typically have bed surfaces that are relatively unarmored compared to the substrate below, while gravel bed streams in humid and snowmelt areas typically have well-armored surfaces. The degree of armoring can be characterized in terms of an armor ratio defined as the ratio of the surface median size to the substrate median size. A set of field data shows desert ephemeral gravel bed streams with armor ratios ranging from 0.5 to 2.4 and with an average value of 1.2. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
198
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(209 citation statements)
references
References 33 publications
11
198
0
Order By: Relevance
“…Also, the grain size distribution of the bed material and, in particular, the increase in sand content plays a role in the armoring process by reducing vertical sorting (Marion and Fraccarollo, 1997) or by reducing surface roughness and facilitating the rearrangement of the bed particles (Curran and Waters, 2014). Another aspect is the influence of different flow rates on the development of the armor (Hassan et al, 2006;Guney et al, 2013). Hassan et al (2006) indicated a general increase in the armoring degree with an increase in the flow rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the grain size distribution of the bed material and, in particular, the increase in sand content plays a role in the armoring process by reducing vertical sorting (Marion and Fraccarollo, 1997) or by reducing surface roughness and facilitating the rearrangement of the bed particles (Curran and Waters, 2014). Another aspect is the influence of different flow rates on the development of the armor (Hassan et al, 2006;Guney et al, 2013). Hassan et al (2006) indicated a general increase in the armoring degree with an increase in the flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect is the influence of different flow rates on the development of the armor (Hassan et al, 2006;Guney et al, 2013). Hassan et al (2006) indicated a general increase in the armoring degree with an increase in the flow rate. They also showed that temporally varying flows lead to stronger armoring than steady flows.…”
Section: Introductionmentioning
confidence: 99%
“…This term has an order of magnitude 10 -5 while the S0 or Se has an order of 10 -3 (Graf and Altınakar, 1998). It was assumed that the spatial variation of velocity in the channel is negligible (Powell et al 2001, Hassan et al 2006. Therefore the term…”
Section: The Slope Method Saint-venant Equations (U*un and U*sv)mentioning
confidence: 99%
“…Under unsteady flow conditions, some researchers prefer to estimate the shear stress using the depth-slope product rule corresponding to normal (steady, uniform) flow especially when the purpose of their study is to focus on overall parameters rather than local parameters (Hassan et al 2006, Güney et al 2013 or prefer to neglect the contribution of velocity gradient to energy slope (Powell et al 2001). Qu (2002), Song and Graf (1996) and Afzalimehr et al (2007) used some of these methods in unsteady flows, but the comparison of these methods is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since turbidity current occurring due to sediment laden reduces dam storage capacity, turbidity current and carrying sediment laden also can be an important parameter. Numerous researches related to density current were carried out both experimentally and theoretically by Stefan (1973), Garcia (1993Garcia ( , 1994, Bradford et al (1997), Lee and Yu (1997), Yu et al (2000), Parker (2003, 2006), Wright and Parker (2004), Violet et al (2005), Lamb et al (2004), De Cesare et al (2006, Hassan et al (2006) and Toniolo et al (2006). However, at present, new master projects include many consecutive dam constructions.…”
Section: Introductionmentioning
confidence: 99%